Resection of an Embolized Cirsoid Aneurysm With Intracranial Venous Drainage: 2-Dimensional Operative Video. Issue 3 (5th March 2019) - Heiferman, Daniel M; Syed, Hasan R; Li, Daphne; Rothstein, Brian D; Shaibani, Ali; Tomita, Tadanori
Abstract: Cirsoid aneurysms, also known as scalp arteriovenous malformations (AVM), are rare congenital extracranial vascular anomalies that often present as an enlarging pulsatile scalp mass. A 14-yr-old male presented with a pulsatile scalp lesion that was first noticed 3 yr prior and had progressively enlarged. No history of trauma was reported. MRI demonstrated a 4 cm wide and 2 cm tall nidus and catheter angiography was performed to further define the vascular supply and drainage. The patient underwent transvenous endovascular embolization followed by surgical excision via a bicoronal incision, as shown in this operative video. Care was taken to identify, cauterize, and transect feeding vessels from the superficial temporal, supratrochlear, and supraorbital arteries circumferentially to completely devascularize and resect the galeal nidus from overlying scalp tissue and underlying pericranium. Previously unreported in the literature, transosseous emissary veins partially draining the lesion were noted on angiography and were waxed thoroughly during surgery. Six-month follow-up examination demonstrated a well-healed incision without evidence of AVM recurrence. The unique venous drainage of this cirsoid aneurysm highlights the value of diagnostic angiography to fully characterize these rare and complex vascular lesions prior to pursuing definitive treatment.  IRB approval was obtained from the Ann & Robert H. Lurie Children's Hospital of Chicago Institutional Review Board (IRB #2018-1799). The IRB waives the requirement of obtaining informed consent for this study in accordance with 45 CFR 46.116(d).